Fashion design course - Faerm, Steven (B.E.S. Publishing, 2017)
An introduction to fashion design offers practical exercises and interviews with industry professionals to help readers create their own collections and discover their unique design vision.
Na obálce: Principles, practice, and techniques: the practical guide for aspiring fashion designers
Keywords: módní návrhářství; fashion design; příručky; handbooks, manuals, etc